2014
DOI: 10.3141/2458-01
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Illuminance Transition at Highway Tunnel Portals on Basis of Visual Load

Abstract: Highway tunnel entrances and exits are accident-prone locations, especially in the daytime, primarily because of the sharp transitions in lighting in these areas. Therefore, a rational assessment of lighting transitions at tunnel portals is the key to ensuring traffic safety. This study used the EMR-8B eye-tracker system to monitor the pupil changes of eight selected drivers as they drove through 26 typical highway tunnels. The test results showed a power function relationship between drivers’ pupil areas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Dong et al [21] revealed that LEDs with correlated color temperatures (CCTs) ranging from 4000 to 4500 K are preferable for tunnel entrance lighting. Zhi et al [22] evaluated the safety of illuminance transitions at highway tunnel portals on the basis of visual load. Zhou et al [23] simulated human visual perception under nighttime illuminance.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al [21] revealed that LEDs with correlated color temperatures (CCTs) ranging from 4000 to 4500 K are preferable for tunnel entrance lighting. Zhi et al [22] evaluated the safety of illuminance transitions at highway tunnel portals on the basis of visual load. Zhou et al [23] simulated human visual perception under nighttime illuminance.…”
Section: Introductionmentioning
confidence: 99%
“…L. Dong et al revealed that light-emitting diodes (LEDs) with correlated color temperatures (CCTs) ranging from 4000-4500 K are preferable for tunnel entrance lighting [21]. G. Zhi, et al evaluated the safety of illuminance transition at highway tunnel portals on basis of visual load [22].N. Zhou et al simulated human visual perception under nighttime illuminance [23].…”
Section: Introductionmentioning
confidence: 99%
“…Above existing studies primarily focus on the analysis of the characteristics of the drivers' eye movement such as the gaze, saccade, and pupil changes in highway tunnels [14,15] and urban tunnels [16,17]. Unfortunately, relevant studies on the drivers' visual characteristics in urban undersea tunnels is lacking at this stage.…”
Section: Introductionmentioning
confidence: 99%